The Credibility of Imam Al-Shafi’i in His Journey for Finding Scientific Knowledge - Mohd Hasrul Shuhari, Muhammad Nasri Hassan Basri, Nur Solehah Mohd Yazid, Siti Hajar Mohamad Yusoff, Norhashimah Yahya, Mohd Manawi Mohd Akib (International Journal of Advanced Science and Technology, 2020)
Imam al-Shafi'i is well-known as one of the greatest scholars in the history of Islamic knowledge. There were many aspects which caused him  to learn various types of knowledge which not only limited to fiqh subject, but also in many other subject areas. This study was conducted as part of an effort to highlight the credibility of Imam al-Shafie in his journey in seeking scientific knowledge. The researchers conduct descriptive qualitative research in the aspects of data collection and data analysis. The results show that there are several key aspects that have been the catalyst for Imam Shafi’i through his scholar journey until his birth as a credible figure in the area of scientific knowledge from Islamic perpective.Keywords: Imam Shafi’i, Scientific Knowledge, Islamic Education, Ethics